2017
DOI: 10.1007/s10021-017-0153-9
|View full text |Cite
|
Sign up to set email alerts
|

Shellfish Reefs Increase Water Storage Capacity on Intertidal Flats Over Extensive Spatial Scales

Abstract: Ecosystem engineering species can affect their environment at multiple spatial scales, from the local scale up to a significant distance, by indirectly affecting the surrounding habitats. Structural changes in the landscape can have important consequences for ecosystem functioning, for example, by increasing retention of limiting resources in the system. Yet, it remains poorly understood how extensive the footprint of ecosystem engineers on the landscape is. Using remote sensing techniques, we reveal that depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…The Oosterschelde is a coastal bay (tidal range at the study site 3 m, salinity 30 ppt) that suffers from eroding intertidal flats, due to infrastructural works (i.e. construction of a storm-surge barrier) in the 1980s (Nienhuis and Smaal 1994;Walles et al 2016a). Tidal flats are eroding on average 1 cm.…”
Section: Study Case 2: Oyster Reefs As Protection Against Tidalmentioning
confidence: 99%
“…The Oosterschelde is a coastal bay (tidal range at the study site 3 m, salinity 30 ppt) that suffers from eroding intertidal flats, due to infrastructural works (i.e. construction of a storm-surge barrier) in the 1980s (Nienhuis and Smaal 1994;Walles et al 2016a). Tidal flats are eroding on average 1 cm.…”
Section: Study Case 2: Oyster Reefs As Protection Against Tidalmentioning
confidence: 99%
“…2014 1 jan-28 feb (2x pw); 1 maa-31 okt (3x pw); 1 nov-31-dec (2x pw); 2015 1 jan-28 feb (2x pw); 2016 1 jan-31-dec (2x pw) (Kerstens, Giannopapa et al 2017) (Wal, Vullings et al 2017) 2018 (Fokker, van Leijen et al 2018) (Nieuwhof, van Belzen et al 2018) Bron ( Ground surface dynamics is one of the processes influencing the future of the Wadden Sea area.…”
Section: Vergroten Internationale Positiementioning
confidence: 99%
“…For example, Nieuwhof et al. (2018) detected changes in water storage capacity as the distance from shellfish reefs increased, and Li et al. (2019) identified the boundary of the Antarctic Intermediate Waterway.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nieuwhof et al (2018) detected changes in water storage capacity as the distance from shellfish reefs increased, and Li et al (2019) identified the boundary of the Antarctic Intermediate Waterway. In this work, we draw on ideas from the nonparametric statistics and machine learning literature and develop a retrospective change-point estimation method for series of point cloud data that can be applied to segment flow cytometry data.…”
Section: Introductionmentioning
confidence: 99%